IMPLEMENTASI MODEL PEMBELAJARAN PROJECT BASED LEARNING PADA MATERI SUMBER DAN ENERGI UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS III SDN TLOGOMAS 2 KOTA MALANG - Sabu, Silfertina; Fitriyah, Siti Ni'matul; Emqi, Muhammad Fauzy (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low learning outcomes of third-grade students on the material of sources and energy at SDN Tlogomas 2 Malang City, which is characterized by a lack of active involvement and conceptual understanding. The purpose of the research is to improve student learning outcomes through the implementation of the Project Based Learning (PjBL) learning model. This research uses a Classroom Action Research (CAR) approach with two cycles, each including planning, implementation, observation, and reflection. The research subjects consisted of 28 third-grade students. Data were collected through initial tests (pre-test) and final tests (post-test), observation sheets for student and teacher activities, interviews, documentation, and field notes. Quantitative data analysis was carried out by calculating the average value of learning outcomes and the percentage of individual and classical completion, while qualitative data were analyzed to assess student involvement, participation, and response to PjBL. The results showed a significant increase; the average observation of student activities increased from 71.43% in cycle I (sufficient category) to 82.29% in cycle II (good category), while classical completion increased from 64.3% to 82.29%. The implementation of PjBL also encourages collaboration, creativity, and student responsibility in completing projects related to resources and energy. In conclusion, the PjBL model has proven effective in improving student learning outcomes, skills, and active participation, making it a suitable alternative learning strategy in the classroom.